Modern Food Microbiology - Jay, James M.; Loessner, Martin J.; Golden, David A.; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
With 30 revised and updated chapters, the new edition of this classic text brings benefits to professors and students alike who will find new sections on proteobacteria, bottled water, food sanitizers (eletrolyzed oxidating water, ozone, chlorine, activin, chitosans, endolysins, etc.), bicontrol, biosensors quorum sensing, molecular genetic methods of analysis, food safety objectives, noroviruses, and prions. The book builds on the trusted and established sections on food preservation by modified atmosphere, high pressure and pulsed electric field processing, food-borne pathogens, food regulations, fresh-cut produce, new food products, and risk assessment and analysis. In-depth references, appendixes, illustrations, index and thorough updating of taxonomies make this an essential for every food scientist.
Historical Background -- History of Microorganisms in Food -- Habitats, Taxonomy, and Growth Parameters -- Taxonomy, Role, and Significance of Microorganisms in Foods -- Intrinsic and Extrinsic Parameters of Foods That Affect Microbial Growth -- Microorganisms in Foods -- Fresh Meats and Poultry -- Processed Meats and Seafoods -- Vegetable and Fruit Products -- Milk, Fermentation, and Fermented and Nonfermented Dairy Products -- Nondairy Fermented Foods and Products -- Miscellaneous Food Products -- Determining Microorganisms and/or Their Products in Foods -- Culture, Microscopic, and Sampling Methods -- Chemical, Biological, and Physical Methods -- Bioassay and Related Methods -- Food Protection and Some Properties of Psychrotrophs, Thermophiles, and Radiation-Resistant Bacteria -- Food Protection with Chemicals, and by Biocontrol -- Food Protection with Modified Atmospheres -- Radiation Protection of Foods, and Nature of Microbial Radiation Resistance -- Protection of Foods with Low-Temperatures, and Characteristics of Psychrotrophic Microorganisms -- Food Protection with High Temperatures, and Characteristics of Thermophilic Microorganisms -- Protection of Foods by Drying -- Other Food Protection Methods -- Indicators Of Food Safety and Quality, Principles of Quality Control, and Microbiological Criteria -- Indicators of Food Microbial Quality and Safety -- The HACCP and FSO Systems for Food Safety -- Foodborne Diseases -- to Foodborne Pathogens -- Staphylococcal Gastroenteritis -- Food Poisoning Caused by Gram-Positive Sporeforming Bacteria -- Foodborne Listeriosis -- Foodborne Gastroenteritis Caused by Salmonella and Shigella -- Foodborne Gastroenteritis Caused by Escherichia coli -- Foodborne Gastroenteritis Caused by Vibrio, Yersinia, and Campylobacter Species -- Foodborne Animal Parasites -- Mycotoxins -- Viruses and Some Other Proven and Suspected Foodborne Biohazards.
Keywords: Chemistry; Food -- Biotechnology; Microbiology; Chemistry; Food Science; Microbiology; Electronic books